Quality Analysis on Spatial Planning Pattern of Rural Area in Southern Shaanxi, China - Juan Xu (MDPI AG, 2021)
There have been many studies that have only focused on factors affecting the spatial distribution of rural settlements, without paying attention to their function and scale. China’s mountainous rural area has many problems, such as a fragile ecological environment, poor infrastructure and limited public service facilities. As a result, mountainous rural settlements demonstrate a disorderly and scattered layout. This research takes southern Shaanxi as its research area and uses quantitative and qualitative analysis to analyze the field survey data, revealing the spatial format of rural settlements and its influencing factors. The research results show that: (1) The spatial structure of mountainous settlements can be summarized as falling into three types—agglomeration type, belt type, and dispersion type. The individual settlements are discrete, and the spatial structure of the settlement groups exhibits small-scale clustering in a large area. (2) The influencing factors of spatial structure are ranked thus—geomorphological conditions > population quantity > land use scale. (3) The number of settlements in the study area is constantly decreasing, and their boundaries are gradually shrinking, showing randomly distributed characteristics. (4) A radius of 284.12 m can be used as a measure of the development scope of the village to control the scope of settlement construction. The objective of the research is to classify the spatial structure and propose the most optimal spatial mode in mountainous rural areas.